EX-HTI STRUGGLE IN PASURUAN: Reading the Pattern of Changes in the Strategy of the Ex-HTI Da'wah Struggle - Bakhrul Ulum (IAIN Ponorogo, 2021)
Abstract: This paper discusses the pattern of changes in the ex-HTI da’wah strategy, which describes the process of ex-HTI struggle patterns in Pasuruan. This research is described qualitatively with a descriptive-analytical field study approach and data analysis techniques with the stages of data condensation, data display, and conclusion/verifying. The results of this study indicate that the ex-HTI da’wah struggle in Pasuruan continues to socialize the caliphate da’wah by utilizing digital media during the Covid-19 pandemic by utilizing elders as religious leaders, besides the pattern of changing its da’wah strategy by utilizing majelis taklim, “rumah inspirasi”, Bustanul Amilin institution, and also SDIT.الملخص:تناقش هذه الورقة نمط التغييرات في استراتيجية الدعوة السابقة للحزب الشيوعي الصيني الخلاصة: تناقش هذه الورقة نمط التغييرات في إستراتيجية الدعوة السابقة لحزب HTI ، والتي تصف عملية أنماط النضال السابقة لـ HTI في باسوروان. تم وصف هذا البحث نوعياً باستخدام منهج الدراسة الميدانية الوصفي التحليلي وتقنيات تحليل البيانات مع مراحل تكثيف البيانات وعرض البيانات والاستنتاج / التحقق. تشير نتائج هذه الدراسة إلى أن نضال الدعوة السابقين لحزب التحرير الإسلامي في باسوروان يستمر في التنشئة الاجتماعية لدعوة الخلافة من خلال استخدام الوسائط الرقمية خلال جائحة كوفيد -19 من خلال استخدام كبار السن كقادة دينيين ، إلى جانب نمط تغيير دعوتها. استراتيجية واه من خلال الاستفادة من مجلس التكليم ،